The Rhizoma polypodii Extract Prevents Lipid Peroxidation and Protects the Unsaturated Fatty Acids in the Environment with Radical Sourced Oxidations - Akkaya, Hatice; Yilmaz, Okkes (Gazi Univ, 2015)
The present study investigated protective effects of the Rhizoma polypodii (R.polypodii) extract on unsaturated fatty acids and the prevention of lipid peroxidation (LPO) formation in the Fenton reagent environment.
Keywords: Fenton Reagent; Flavonoids; Lipid Peroxidation; Radical Scavenging Effect; Rhizoma Polypodii